A new interval-valued approximation of interval-valued fuzzy numbers - Ahmadian, Ali; Zainal, S. Z.; Suleiman, Mohamed; Salahshour, Soheil; Senu, Norazak; Godarzi, M. (International Scientific Publications and Consulting Services (ISPACS), 2015)
In this paper, we proposed a new interval-valued approximation of interval-valued fuzzy numbers, which is the best one with respect to a certain measure of distance between interval-valued fuzzy numbers. Also, a set of criteria for interval-valued approximation operators is suggested.